2020
DOI: 10.26434/chemrxiv.12040518.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deferasirox (ExJade): A Fluorescent Pro-Chelator Active Against Antibiotic Resistant Bacteria

Abstract: <p>Deferasirox,<b> ExJade</b>, an FDA-approved treatment for iron overload disorders has been shown to inhibit the growth of both gram-positive and -negative bacteria through iron (Fe(III)) chelation. Modification of the <b>ExJade</b> framework led to the identification of a new fluorescent platform <b>ExPh </b>and <b>ExBT</b>. Functionalization of the phenol moieties on <b>ExBT</b> with phosphate units afforded a ratiometric fluorescent pro-ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The Fe binding property of Ti(Deferasirox) 2 may play a significant role in its inhibition of MRSA by disrupting Fe bioavailability. This possibility is supported by the recent preprint work by Sessler et al, which demonstrated that a prochelator form of deferasirox could inhibit MRSA up to 70% at 15 µM [4,69]. Ti(Deferasirox) 2 can be viewed as a prochelator with it displaying high extracellular stability and intracellular Fe-induced transmetalation [36].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The Fe binding property of Ti(Deferasirox) 2 may play a significant role in its inhibition of MRSA by disrupting Fe bioavailability. This possibility is supported by the recent preprint work by Sessler et al, which demonstrated that a prochelator form of deferasirox could inhibit MRSA up to 70% at 15 µM [4,69]. Ti(Deferasirox) 2 can be viewed as a prochelator with it displaying high extracellular stability and intracellular Fe-induced transmetalation [36].…”
Section: Discussionmentioning
confidence: 89%
“…Given the central role that essential metals can play in microbial growth and the distinctive chemistry that can be facilitated by metals coupled with the varied structures and properties that they can adopt from ligand complexation, metal-centered antimicrobial strategies are an exciting new research avenue. One approach is developing compounds that can uniquely perturb the essential metal homeostasis within pathogenic microbes and possibly even attenuate their bioavailability [ 1 , 2 , 3 , 4 ]. Another approach is assessing the therapeutic potential of metals in ion or complex form.…”
Section: Introductionmentioning
confidence: 99%
“…9 On the other hand, the tridentate chelator deferasirox (DFX or ICL670, I of Scheme 1), initially reported in 1999, 10 was the first oral medication for iron overload to be accepted by the Food and Drug Administrations (FDA) in 2005, and later by the European Medicines Agency in 2006. 11,12 Recently, DFX combined with deferiprone has been reported to eliminate thallium from rats’ organs. 13 Recent investigations have shown that DFX can be used as an effective chemotherapeutic, 14,15 antifungal, 16 and antimicrobial agent.…”
Section: Introductionmentioning
confidence: 99%